2006
DOI: 10.1093/jac/dkl422
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence, prevalence and genetic environment of CTX-M  -lactamases in Enterobacteriaceae from Indian hospitals

Abstract: In contrast with other studies where greater diversity exists, CTX-M-15 was the only CTX-M ESBL produced in this Indian collection of unrelated E. coli and K. pneumoniae. This is the first systematic survey report from India detecting CTX-M-type beta-lactamases This is also the first report indicating such high mobility/diversity of insertion of IS26 in close association with bla(CTX-M) in a single bacterial collection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
77
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(93 citation statements)
references
References 14 publications
14
77
2
Order By: Relevance
“…By MIC, majority of the isolates conferred high resistance to cefotaxime ([256 to [1,024 lg/ml) as well as to ceftazidime (16 to [256 lg/ml). Thus, MIC determination to cefotaxime and ceftazidime is not a reliable approach for CTX-M, this correlates with other studies [19].…”
Section: Antibiotic Susceptibility Testingsupporting
confidence: 85%
See 1 more Smart Citation
“…By MIC, majority of the isolates conferred high resistance to cefotaxime ([256 to [1,024 lg/ml) as well as to ceftazidime (16 to [256 lg/ml). Thus, MIC determination to cefotaxime and ceftazidime is not a reliable approach for CTX-M, this correlates with other studies [19].…”
Section: Antibiotic Susceptibility Testingsupporting
confidence: 85%
“…A variant of the CTX-M-3 enzyme, designated CTX-M-15 was reported in May 2000 [3]. CTX-M-15 appears to be the predominant ESBL in northern India [19,24,25]. Jemima et al [22] reported prevalence of CTX-M-1 type gene in 58.3% Klebsiella spp.…”
Section: Molecular Analysis By Pcrmentioning
confidence: 99%
“…IdentiÞ cation of CTX-M-15 in four strains of Enterobacteriaceae by sequence analysis correlated well with the earlier Þ ndings from north India. [5,6] In conclusion, this study documents the presence of CTX-M type β lactamase among the ESBLs in this tertiary care hospital in south India.…”
Section: Discussionsupporting
confidence: 51%
“…[4] Isolates producing ESBLs have not been characterized in most of the earlier studies except two studies from North India, which have reported CTX-M-15 β lactamases in isolates of Enterobacteriaceae. [5,6] Although ESBL phenotypes have been reported from south India, there is no information on their molecular types. Hence, the present study was undertaken to characterize the β-lactamases in multidrugresistant clinical isolates of Enterobacteriaceae by molecular techniques.…”
mentioning
confidence: 99%
“…CTX-M-15 is known to be an ESBL that has peculiar association with community-onset E. coli infections. Ensor et al [14] have shown that in India bla CTX-M-15 are the most prevalent than any other type and it is widely distributed in both North and South India. They also reported that the Indian population represented a significant reservoir and source of bla CTX-M-15 [14].…”
Section: Introductionmentioning
confidence: 99%